Effect of exercise on the pulmonary system in proliferative phase of menstrual cycle in a group of perimenopausal women - Amrith Pakkala; C P Ganashree; T Raghavendra (Wolters Kluwer Medknow Publications, 2014)
Background: Hormonal levels influence dynamic lung function parameters. Significant increase in both progesterone (37%) and estradiol (13.5%); where as, no change in plasma follicle stimulating hormone (FSH) and luteinizing hormone (LH) was observed in exercising women in previous studies. Therefore, this study was intended to see the limitations of the pulmonary system in adaptability to exercise in proliferative phase of menstrual cycle in perimenopausal women. Material and Methods: The present study was conducted as a part of cardiopulmonary efficiency studies on two groups of nonathletes (n = 10) and athletes (n = 10) comparable in age and sex. Menstrual history was ascertained to confirm proliferative phase of menstrual cycle. Dynamic lung functions were measured in both groups before exercise and immediately after exercise. Results: It was observed that exercise per se does not cause a statistically significant change in dynamic lung function parameters maximum mid-expiratory flow (MMEF), peak expiratory flow rate (PEFR), and MEF 25-75% in either of the groups. Conclusion: This finding supports the hypothesis that the respiratory system is not normally the most limiting factor in the delivery of oxygen even under the predominant influence of estrogen in proliferative phase, which is further accentuated by exercise.